Clinical, Immunological, and Molecular Findings in 57 Patients With Severe Combined Immunodeficiency (SCID) From India - Aluri, Jahnavi; Desai, Mukesh; Gupta, Maya; Dalvi, Aparna; Terance, Antony; Rosenzweig, Sergio D.; Stoddard, Jennifer L.; Niemela, Julie E.; Tamankar, Vasundhara; Mhatre, Snehal; Bargir, Umair; Kulkarni, Manasi; et al. (Frontiers in Immunology, 2019)
Severe combined immunodeficiency (SCID) represents one of the most severe forms of primary immunodeficiency (PID) disorders characterized by impaired cellular and humoral immune responses. Here, we report the clinical, immunological, and molecular findings in 57 patients diagnosed with SCID from India. Majority of our patients (89%) presented within 6 months of age. The most common clinical manifestations observed were recurrent pneumonia (66%), failure to thrive (60%), chronic diarrhea (35%), gastrointestinal infection (21%) and oral candidiasis (21%). Hematopoietic Stem Cell Transplantation (HSCT) is the only curative therapy available for treating these patients. Four patients underwent HSCT in our cohort but had a poor survival outcome. Lymphopenia (absolute lymphocyte counts/µL<2500) was noted in 63% of the patients. Based on immunophenotypic pattern, majority of the cases were T-B- SCID (39%) followed by T-B+ SCID (28%). MHC class II deficiency accounted for 10.5% of our patient group. A total of 49 patients were molecularly characterized in this study and 39 novel variants were identified in our cohort. The spectrum of genetic defects in our cohort revealed a wide genetic heterogeneity with the major genetic cause being RAG1/2 gene defect (n=12) followed by IL2RG (n=9) and JAK3 defects (n=9). Rare forms of SCID like Purine nucleoside phosphorylase (PNP) deficiency, reticular dysgenesis, DNA-Protein Kinase (DNA-PKcs) deficiency, six cases of MHC class II deficiency and two ZAP70 deficiency were also identified in our cohort. Fourteen percent of the defects still remained uncharacterized despite the application of next generation sequencing. With the exception of MHC class II deficiency and ZAP70 deficiency, all SCID patients had extremely low T cell receptor excision (TRECs) (<18 copies/µL).